Comorbidity in in patients with relapsing-remitting multiple sclerosis - O.V. Somilo; S.O. Makarov; O.I. Kalbus (Medičnì Perspektivi, 2024)
Multiple sclerosis is a chronic autoimmune inflammatory disease that affects the brain and spinal cord. The most common form of this disease according to the type of its course is relapsing-remitting multiple sclerosis. Comorbidity in multiple sclerosis is an urgent problem of modern neurology, since it can influence such factors as the time of diagnosis, the rate of disease progression and the rate of patient disability, the number of exacerbations and the patient’s quality of life. The purpose of the work was to study and characterize comorbidity in patients with relapsing multiple sclerosis. To conduct this study 105 patients with a diagnosis of relapsing-remitting multiple sclerosis were enrolled. All patients were assessed using the Multiple Sclerosis Neurological Disability Severity Scale (EDSS). Study participants were divided into two groups – Group 1 and Group 2 – based on EDSS scores. Separately, study participants were divided into groups based on the principle of receiving pain-modifying therapy. In the 1st study group, concomitant diseases were in 57 (78.1%) patients, in the 2nd group – in 100% (p=0.010). In patients who did not receive pain-modifying therapy, 57 (98.3%) of those examined had concomitant diseases, in those who received such treatment – in 32 (68.1%), which was statistically significantly less (p<0.001). In the first place in terms of the frequency of concomitant pathology among all examined patients were diseases of the gastrointestinal tract, which also dominated in the 1st and 2nd observation groups, in the second place – diseases of the urinary system, in the third place – eye diseases, and in the last place, by the frequency of concomitant diseases – cardiovascular diseases. Comorbidity in multiple sclerosis is an extremely relevant problem in modern neurology due to its significant impact on the clinical picture of the disease, its course and the degree of disability of the patient. Digestive system disease is one of the most common comorbid conditions in multiple sclerosis. The number of patients with comorbid conditions is higher among patients with a moderate degree of disability and among patients not taking disease-modifying therapy, but the relationship between the degree of disability, treatment and comorbid conditions requires further study.